2021
DOI: 10.1111/sjoe.12426
|View full text |Cite
|
Sign up to set email alerts
|

Living in the Shadow of the Past: Financial Profiles and Well‐Being*

Abstract: We here consider the link between individual financial profiles over time and well-being, as measured by life satisfaction. We in particular look at annual self-reported financial worsening and improvement information for over 25,000 individuals in Australian panel data from 2002 to 2017. We first find that satisfaction falls (rises) with a contemporaneous major financial worsening (improvement), with worsening having the larger influence. Second, the experience of these financial events in the past continues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We have Westfall-Young stepdown adjusted p-values for the estimates presented in Figure2using the Stata wyoung program(Jones et al, 2019). The adjusted p-values indicate that the association between unemployment and poor mental health remains statistically significant at the 5% level for women aged 20-29.6 The estimated impacts are more likely driven by increases in unemployment (economic downturns) than by decreases in unemployment.Negative economic shocks have been shown to have larger impact on mental wellbeing than positive shocks(Boyce et al, 2013;Clark et al, 2021) 7 Although employment type is time-varying, it is unaffected by the area unemployment rate in our sample. The estimated unemployment effect for young women equals 0.0004 (p = 0.815).8 The percentage of observations in our sample occurring in areas in which the unemployment rate is <3%, 3-6%, 6-9% and >9% equal 9.2%, 54.7%, 30.8% and 5.3%, respectively.9 Respondents are asked to recall their parent's occupation when they were aged 14.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…We have Westfall-Young stepdown adjusted p-values for the estimates presented in Figure2using the Stata wyoung program(Jones et al, 2019). The adjusted p-values indicate that the association between unemployment and poor mental health remains statistically significant at the 5% level for women aged 20-29.6 The estimated impacts are more likely driven by increases in unemployment (economic downturns) than by decreases in unemployment.Negative economic shocks have been shown to have larger impact on mental wellbeing than positive shocks(Boyce et al, 2013;Clark et al, 2021) 7 Although employment type is time-varying, it is unaffected by the area unemployment rate in our sample. The estimated unemployment effect for young women equals 0.0004 (p = 0.815).8 The percentage of observations in our sample occurring in areas in which the unemployment rate is <3%, 3-6%, 6-9% and >9% equal 9.2%, 54.7%, 30.8% and 5.3%, respectively.9 Respondents are asked to recall their parent's occupation when they were aged 14.…”
mentioning
confidence: 77%
“… The estimated impacts are more likely driven by increases in unemployment (economic downturns) than by decreases in unemployment. Negative economic shocks have been shown to have larger impact on mental wellbeing than positive shocks (Boyce et al., 2013; Clark et al., 2021) …”
mentioning
confidence: 99%
“…In contrast, positive financial and economic events tend to have small effects on subjective wellbeing, indicative of loss aversion: the idea that 'losses loom larger than gains' (Tversky and Kahneman 1979, p. 279). 10 Frijters, Johnston and Shields (2011), Kettlewell et al (2020), Clark, D'ambrosio and Zhu (2021) and others have identified significant effects of the 'major improvement in finances' event, but effect sizes are relatively small. Similarly, positive labour market events have been shown to have small or near-zero effects.…”
Section: Estimated Effects Of Shocks On Wellbeingmentioning
confidence: 99%
“…The subjective 'major worsening in finances' event in HILDA has been repeatedly found to have a large effect on subjective wellbeing outcomes. 9 Recently, Clark, D'ambrosio and Zhu (2021) conclude that the first-period effect of this adverse event on overall life satisfaction (-10 scale) is almost −0.4, and roughly four-times larger than the 'major improvement in finances' event. Adaptation to the negative financial shock seems to take around 2-3 years, and is particularly harmful for people at the lower end of the wellbeing distribution.…”
Section: Estimated Effects Of Shocks On Wellbeingmentioning
confidence: 99%
“…However, this effect is more pronounced when the type of debt is high-cost and unsecured (Hojman, Miranda, and Ruiz-Tagle 2016; Loibl et al 2022; Meltzer et al 2013), where there are multiple sources of debt (Meltzer et al 2013), and where debts are persistently high over time (Clayton et al 2015; Gunasinghe et al 2018; Hojman et al 2016; Sun and Houle 2020). Similarly, studies based on subjective measures such as capacity or difficulty to pay (ten Have et al 2021) or financial worry and rumination (de Bruijn and Antonides 2020) find an increased likelihood of mental disorder and lower levels of life satisfaction irrespective of the type (Loibl et al 2022), which is heightened when persistent over time (Clark, D’Ambrosio, and Zhu 2021; ten Have et al 2021).…”
Section: Background Literaturementioning
confidence: 99%